(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
Now a days side road emergency like tire puncher, is a problem commonly observed in cars. Conventional car jacks uses mechanical advantage to allow a human to lift a vehicle by manual force. This paper studies the modification of the current toggle jack by incorporating an electric DC motor in the screw in order to make load lifting easier for emergency use with using power of car battery (12 Volts). The purpose of this work is to modify the existing car jack in order to make the operation easier, safer and more reliable in order to save individual internal energy and to reduce health risks especially back ache problems associated with doing work in a bent or squatting position for a long period of time. Fabrication work are using with drilling, grinding, and welding machine. Implementation of design will solve problem associated with ergonomics Car battery D.C Motor, propeller shaft, jack, screw.